Supervivencia, testimonio y envejecimiento: la escritura necrológica de Mark Twain y Roland Barthes = Survival, Testimony, and Ageing: Mark Twain and Roland Barthes’ obituary prose - Rodríguez Rodríguez, Félix (Estudios Ingleses de la Universidad Complutense, 2004)
This paper explores the ways in which the experience of surviving might enable us to consider the question of death in old age. Some contemporary philosophers (Vladimir Jankélévitch, Emmanuel Levinas, for example) have insisted that to survive, most particularly when it involves the loss of relatives and friends, provides the only means available to know the otherwise inconceivable negativity and absolute irrevocability of death. In this respect, and insofar as old age can be figured as accumulation of losses, to survive, as opposed to or supplementing other notions, becomes a crucial issue to re-evaluate how the ageing person, as a survivor, comes to terms with the distressing thought of his own approaching death. Drawing on Roland Barthes’s Camera Lucida and Mark Twain’s Autobiography, I focus on one of the ineludible ethical duties of survivors, that of testifying to the other’s memory to whom they owe a debt of gratitude. In keeping the testimony of the others who have died, thus performing their responsibilities as survivors, the ageing Barthes and Twain might achieve an acute consciousness of the irrevocable character of their own death.